The Damage of ZnO Arrester Block Due To Multiple Impulse Currents - Tarcicius Haryono; K. Tunggul Sirait; Tumiran Tumiran; Hamzah Berahim (Universitas Ahmad Dahlan, 2011)
A lightning arrester installed in an electrical power system is designed to protect some electrical equipment against damage due to lightning impulse strike. However, if there is a multiple impulse current striking a lightning arrester, it may damage the lightning arrester itself and then, as a result, it cannot provide lightning protection to the electrical equipment anymore. In this research, three peak values of lightning impulse current,which were 600, 1300, and 2500A, each of which had 5 repetitive impulse current, was applied to a 5000A (1p.u.) ZnO block of a 24kV nominal voltage lightning arrester having seven ZnO block units. The results of research showed that by applying impulse current of the order of 600(0.12), 1300(0.26), dan 2500(0.5) A(p.u.), making the ZnO block damage as much as 26.58, 50, and 100% concecutively. In addition, the damage of the ZnO block appeared as permanen low value of residual voltage as low as more than 5% of the new ZnO block residual voltage. If the ZnO block is still being used in a lightning arrester in electrical power system, it may result in the opening of a circuit breaker and possibly making electrical power outages from a number of electrical power customers.